2017
DOI: 10.1155/2017/8290804
|View full text |Cite
|
Sign up to set email alerts
|

Custom-Made Alumina Ceramic Total Talar Prosthesis for Idiopathic Aseptic Necrosis of the Talus: Report of Two Cases

Abstract: Two women aged 65 years and 78 years presented to our center with idiopathic necrosis of the talus. In both cases, imaging examinations showed collapse and sclerotic changes of the talar body caused by the necrosis. Both women underwent resection and placement of a third-generation custom-made alumina ceramic total talar prosthesis. Immobilization of the ankle in a short-leg cast for 3 weeks was followed by early rehabilitation. One year and 6 months after surgery, both women were able to walk without pain. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 22 publications
0
22
0
Order By: Relevance
“…The image is segmented and an STL file is created and then mirrored, which is followed by either milling or 3D printing of the talar prosthesis. Clearly this process is possible as noted by many published reports (Harnroongroj and Vanadurongwan, 1997 ; Tanaka et al, 2003 ; Stevens et al, 2007 ; Taniguchi et al, 2012 , 2015 ; Harnroongroj and Harnroongroj, 2014 ). However, this design process, including steps from 3D geometry preparation to external implant manufacturing can take many weeks to months based on surgical experience, which increases the time between surgical treatment decision to proceed with talar replacement and the actual surgical procedure.…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…The image is segmented and an STL file is created and then mirrored, which is followed by either milling or 3D printing of the talar prosthesis. Clearly this process is possible as noted by many published reports (Harnroongroj and Vanadurongwan, 1997 ; Tanaka et al, 2003 ; Stevens et al, 2007 ; Taniguchi et al, 2012 , 2015 ; Harnroongroj and Harnroongroj, 2014 ). However, this design process, including steps from 3D geometry preparation to external implant manufacturing can take many weeks to months based on surgical experience, which increases the time between surgical treatment decision to proceed with talar replacement and the actual surgical procedure.…”
Section: Introductionmentioning
confidence: 63%
“…This can result in adequate pain relief but severe ankle and hindfoot stiffness, making ambulation difficult. Due to the significant functional limitations of this surgical procedure, some surgeons have developed custom talar bone implants using metal or ceramic for these patients (Tanaka et al, 2003 ; Taniguchi et al, 2015 ; Katsui et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Early case reports have shown good clinical outcomes, but mainly in isolated case reports. 10,11 Other authors have shown that total talus replacements can also be used as salvage for total ankles that have significant talar subsidence. [13][14][15] Recently, authors from our institution have shown good radiographic outcomes following third-generation custom 3D printed total talus replacement for talar AVN 8 ; however, there have not been clinical outcomes reported outside of scattered case reports, with the largest series being only 2 patients.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] Recently, authors from our institution have shown good radiographic outcomes following third-generation custom 3D printed total talus replacement for talar AVN 8 ; however, there have not been clinical outcomes reported outside of scattered case reports, with the largest series being only 2 patients. 10…”
Section: Introductionmentioning
confidence: 99%
“…The literature, with respect to the use of third-generation TTR in the setting of talar AVN, has yet to report a complication necessitating conversion to a salvage arthrodesis. 12,14,15 The use of 3D printing, and specifically the EBM method, has been very efficient in reducing the time between planning and implantation of TTR (in comparison to the ceramic third-generation TTR used by Taniguchi et al 12 ). With respect to our study, we have found this method of contralateral CAD inversion and EBM to be suitable for TTR in AVN patients.…”
Section: Discussionmentioning
confidence: 99%